2019
DOI: 10.1037/ser0000263
|View full text |Cite
|
Sign up to set email alerts
|

Empirically-guided assessment of complex trauma for children in foster care: A focus on appropriate diagnosis of attachment concerns.

Abstract: Complex trauma is defined as repeated or prolonged exposure to traumatic events perpetrated within the caregiving relationship during early childhood. Diagnostic decision making is challenging for this vulnerable population, given the widespread impact of these experiences across domains of developmental, social, emotional, and behavioral functioning. One domain, attachment, receives considerable attention for youth within the child welfare system, leading to frequent diagnosis of attachment disorders (i.e., r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…A previous study, also part of the current mental health project on adolescents in Norwegian RYC, revealed that 78.1% of girls and 60.4% of boys self-reported exposure to maltreatment, and the authors concluded that virtually all had likely experienced some form of neglect [ 33 ]. Moreover, adolescents in the current mental health project have reported high levels of parental chronic illness, mental illness or drug use [ 29 ], indicating increased risk of pathogenic care prior to out-of-home placement [ 10 ]. Furthermore, serious neglect was reported for 86% of school-aged foster children in Norway [ 34 ], a group regarded as exposed to less risk than adolescents in RYC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study, also part of the current mental health project on adolescents in Norwegian RYC, revealed that 78.1% of girls and 60.4% of boys self-reported exposure to maltreatment, and the authors concluded that virtually all had likely experienced some form of neglect [ 33 ]. Moreover, adolescents in the current mental health project have reported high levels of parental chronic illness, mental illness or drug use [ 29 ], indicating increased risk of pathogenic care prior to out-of-home placement [ 10 ]. Furthermore, serious neglect was reported for 86% of school-aged foster children in Norway [ 34 ], a group regarded as exposed to less risk than adolescents in RYC.…”
Section: Methodsmentioning
confidence: 99%
“…Although there is growing evidence that RAD and DSED symptoms may persist into adolescence and early adulthood [5][6][7][8][9], controversy remains regarding their diagnostic classification. Whereas some denominate RAD and DSED as valid diagnostic constructs in adolescence, others question whether symptoms of RAD and DSED may then be better conceptualized as more common psychiatric disorders [2,10]. Hitherto, RAD and DSED have been evidenced as distinct from other psychopathology until middle childhood [11][12][13][14][15][16], but their discriminant validity in adolescence remains unstudied.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood maltreatment and neglect are associated with a wide range of psychiatric disorders and psychosocial problems [1][2][3] and may, in severe cases, cause reactive attachment disorder (RAD) and disinhibited social engagement disorder (DSED) [4]. Distinguishing between various health effects of childhood adversity may be clinically challenging, and there is a particular risk and tendency to misdiagnose RAD and DSED [5,6], either by the under-identification of common psychiatric disorders and neurodevelopmental problems and the over-identification of attachment problems [5,[7][8][9] or vice versa [10,11]. Misdiagnosis may result in missed treatment and developmental support, prolonging individual suffering, functional impairment, and societal costs.…”
Section: Introductionmentioning
confidence: 99%
“…Complex traumas experienced by children are often perpetrated by their primary attachment figures and can hence severely impact this relationship and attachment representations (John et al, 2019). Through interactions with attachment figures, children develop internal working models of themselves and their environment, and learn to interact with others and understand their own value and worth.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they may not have learned how to properly regulate their emotions in times of distress (Cook et al, 2005;Van Der Kolk, 2005). Due to the importance of attachment in relation to (complex) trauma (John et al, 2019), children in foster care are particularly interesting. They are removed from both their attachment figures and the traumatic environment, while simultaneously placed with new parental figures.…”
Section: Introductionmentioning
confidence: 99%